Congenital Milia En Plaque. Issue 4 (10th June 2016) - Wang, Annie R.; Bercovitch, Lionel
Abstract: Milia en plaque is a rare, benign, localized, entity typically seen in adults after the third decade of life. Although there have been a few cases described in children, we describe the first case in a newborn.